Barriers to vaccination in Latin America: A systematic literature review. Issue 3 (16th January 2020) - Guzman-Holst, Adriana; DeAntonio, Rodrigo; Prado-Cohrs, David; Juliao, Patricia
Highlights: Individual/group influence is the main vaccination barrier in Latin America. Low socio-economic group, less educated and age contribute to low vaccine uptake. Education and trust in healthcare professionals enhances vaccine acceptance. More data is needed within target population subgroups, countries and vaccine type. Abstract: Current vaccination coverage rates in Latin America and the Caribbean (LAC) are lower than the region-wide rates set by the Pan American Health Organization. To improve vaccination uptake, it is crucial to identify barriers to vaccination. We conducted a systematic literature review to identify the key barriers to vaccination in the LAC region, and to classify and quantify factors affecting vaccination coverage using the barrier categories outlined by the Strategic Advisory Group of Experts (SAGE) working group. We mapped knowledge gaps in the understanding of region-specific and population-specific vaccine hesitancy. Nine databases (Medline via PubMed, Web of Science, LILACS, MedCarib, SciELO, Scopus, PATH, SAGE Online and Google Scholar) were searched for articles published in English, Spanish and Portuguese up to 15 July 2017. A total of 6867 articles were identified of which 75 were included in the review. Majority of the articles were quantitative in nature and nearly half from Brazil. Many other countries in LAC have limited published evidence on barriers to vaccination. The most commonly investigated target population was parents (of children <8 years of age [yoa] and adolescents 9–10 yoa) but there was a balance in the number of publications that reported on influenza, childhood and human papillomavirus vaccination. There was limited direct evidence which reported insights on the new generation of childhood vaccines (pneumococcal or meningococcal vaccines) or studies targeting adolescents and pregnant women. Among the SAGE barrier categories, 'individual/group influences' were the most frequently reported barrier category (68%) followed by 'contextual influences' (47%). Adverse socioeconomic factors, a low level of education, lack of awareness of diseases and their vaccines, religious and cultural beliefs are commonly cited as obstacles to vaccination acceptance. Additional evidence is needed to fully understand the barriers to vaccination for different target populations, countries in the region and specific vaccine types.